I.N. ULIANOV CHUVASH STATE UNIVERSITY AS AN INNOVATIVE MULTIPROFILE HIGHER EDUCATION INSTITUTION INTEGRATED INTO THE REGIONAL ECONOMY - A. Yu. Aleksandrov (Высшее образование в России)
The article highlights the versatile activities of I.N. Ulianov Chuvash State University. The priority area and the main vector of its development today is training specialists for the formation ofterritorial innovation and technological cluster, the realization ofthe Program for long-term development of electric-power industry in Chuvash Republic, participation in the project for raising the energy efficiency in the region. The paper shows the leading role of the University in the organization ofthe system of higher education, especially in formation ofthe unique continual engineering training system for the youth, coordination and methodical provision ofthis system activity.